1991
DOI: 10.1080/00071669108417430
|View full text |Cite
|
Sign up to set email alerts
|

The response of broiler breeder hens to dietary lysine and methionine

Abstract: 1. Broiler breeder hens were used in an experiment lasting 10 weeks (29 to 38 weeks of age) to measure the responses to dietary lysine and methionine, the main objective being to determine whether the coefficients of response to these amino acids were the same for broiler breeders and for laying pullets. 2. The hens were offered 150 g/d of one of 20 dietary treatments, 10 being lysine-limiting and 10 being methionine-limiting. The diets were mixed by diluting one of two concentrate (summit) mixes with a protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 12 publications
5
32
0
Order By: Relevance
“…In accordance with the results of the present study and those reported by Bowmaker and Gous (1991) methionine requirement for EP was 342 and 355 mg/d, respectively. These amounts were near to the methionine level in the basal diet (322 mg/d), which could provide the minimum methionine requirement for reproductive performance.…”
Section: Discussionsupporting
confidence: 83%
“…In accordance with the results of the present study and those reported by Bowmaker and Gous (1991) methionine requirement for EP was 342 and 355 mg/d, respectively. These amounts were near to the methionine level in the basal diet (322 mg/d), which could provide the minimum methionine requirement for reproductive performance.…”
Section: Discussionsupporting
confidence: 83%
“…Broiler breeders fed intact protein here utilised lysine and methionine for egg production with mean efficiencies of 0.55 and 0.62, respectively, these being lower than the equivalent values estimated for laying hens, but similar to those reported by Bowmaker & Gous (1991) (0.47 for lysine and 0.50 for methionine) and Goddard (1997) (between 0.58 and 0.68 for lysine) in their studies with broiler breeders. It is likely that lysine was not first-limiting in the present trial, given its lower efficiency compared with that for methionine.…”
Section: Discussionmentioning
confidence: 58%
“…The increase in feed intake is an attempt by the birds to consume the required amount of the limiting amino acid to maintain egg production; however, when the deficiency becomes more severe, an increasing feed intake is not possible because the bird would increase heat production (Bowmaker and Gous, 1991). The latter finding is due to the change in the relationship between energy and protein in the diets, which provided more energy intake than necessary to maintain egg production with the lowest met+cys levels.…”
Section: Resultsmentioning
confidence: 65%